Assessments of time diversity rain fade mitigation technique for v-band space-earth link operating in tropical climate - M Saad@Md Saad, Nurul Wahida; Ismail, Ahmad Fadzil; Badron, Khairayu; Mohd Sobli, Nuurul Hudaa; Din, Jafri; Abdul Rahman, Tharek (ETPub, 2013)
Satellite communication systems are moving towards greater capacity. Millimeter wave frequency offers a large bandwidth allocation, requires small antenna size and should not experience congested spectrum environment. Nonetheless, rain posses a grave threat to such satellite communication links especially in tropical region where the hydrometeors can severely affect the signal. Rain is the factor that typically limits the implementation or use of higher frequencies for satellite communications in this region. Time diversity is a promising mitigation technique to countermeasure such impairments. It is envisioned that the technique will not be requiring extensive auxiliary’s equipment. This paper outlines the likely improvement of a future V-band frequency space-Earth link using proposed time diversity (TD) technique. The analyses relating to the performance prediction of a projected satellite communication link in a tropical climate environment assimilating TD scheme are also included. The recovery strategy and its associated equations were deduced reflecting the likely memory capacity requirement of TD. The knowledge will be incorporated accordingly at the receiver with hopes to mitigate attenuation due to rain endured by the propagation path.